Incorporating Low-Dose Epidemiology Data in a Chlorpyrifos Risk Assessment - Julie E. Goodman; Robyn L. Prueitt; Lorenz R. Rhomberg (SAGE Publishing, 2013)
USEPA assessed whether epidemiology data suggest that fetal or early-life chlorpyrifos exposure causes neurodevelopmental effects and, if so, whether they occur at exposures below those causing the current most sensitive endpoint, 10% inhibition of blood acetyl-cholinesterase (AChE). We previously conducted a hypothesis-based weight-of-evidence analysis and found that a proposed causal association between chlorpyrifos exposure and neurodevelopmental effects in the absence of AChE inhibition does not have a substantial basis in existing animal or in vitro studies, and there is no plausible basis for invoking such effects in humans at their far lower exposure levels. The epidemiology studies fail to show consistent patterns; the few associations are likely attributable to alternative explanations. Human data are inappropriate for a dose-response assessment because biomarkers were only measured at one time point, may reflect exposure to other pesticides, and many values are at or below limits of quantification. When considered with pharmacokinetic data, however, these biomarkers provide information on exposure levels relative to those in experimental studies and indicate a margin of exposure of at least 1,000. Because animal data take into account the most sensitive lifestages, the use of AChE inhibition as a regulatory endpoint is protective of adverse effects in sensitive populations.